Customizing Extensor Reconstruction in Vascularized Toe Joint Transfers to Finger Proximal Interphalangeal Joints: A Strategic Approach for Correcting Extensor Lag. Issue 4 (April 2017) - Loh, Charles Yuen Yung; Hsu, Chung-Chen; Lin, Cheng-Hung; Chen, Shih-Heng; Lien, Shwu-Huei; Lin, Chih-Hung; Wei, Fu-Chan; Lin, Yu-Te
Abstract : Background: Vascularized toe proximal interphalangeal joint transfer allows the restoration of damaged joints. However, extensor lag and poor arc of motion have been reported. The authors present their outcomes of treatment according to a novel reconstructive algorithm that addresses extensor lag and allows for consistent results postoperatively. Methods: Vascularized toe joint transfers were performed in a consecutive series of 26 digits in 25 patients. The average age was 30.5 years, with 14 right and 12 left hands. Reconstructed digits included eight index, 10 middle, and eight ring fingers. Simultaneous extensor reconstructions were performed and eight were centralization of lateral bands, five were direct extensor digitorum longus–to–extensor digitorum communis repairs, and 13 were central slip reconstructions. Results: The average length of follow-up was 16.7 months. The average extension lag was 17.9 degrees. The arc of motion was 57.7 degrees (81.7 percent functional use of pretransfer toe proximal interphalangeal joint arc of motion). There was no significant difference in the reconstructed proximal interphalangeal joint arc of motion for the handedness ( p = 0.23), recipient digits ( p = 0.37), or surgical experience in vascularized toe joint transfer ( p = 0.25). The outcomes of different techniques of extensor mechanism reconstruction were similar in terms of extensor lag, arc of motion, and reconstructed finger arc of motion compared with the pretransfer toe proximal interphalangeal joint arc of motion. Conclusion: With this treatment algorithm, consistent outcomes can be produced with minimal extensor lag and maximum use of potential toe proximal interphalangeal joint arc of motion. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV. Abstract : Supplemental Digital Content is available in the text.